Intra-urban cartographic reading of spatial justice and sustainability through residential and tertiary functions in the city of Santander (Cantabria, Spain).: Map - Menéndez González, Gema María; Castillo Salcines, Valentín; de Cos Guerra, Olga (Geographicalia, 2023)
Applied geo-demographic studies are often dependent on the availability of statistical and cartographic sources. This is especially important in detailed studies, as would correspond to intra-urban analyses and, in general, when it is intended to reveal differentiated patterns within the conventional census section. In view of this, the present contribution relies on the use of cadastral cartography of buildings, enriched by means of CAT files and population de-scaling methods at building level, implemented by means of diverse GIS analyses that reveal relevant spatial patterns capable of synthesising the orientation of the different urban pieces in relation to the residential function and the presence of economic activities. In the current context of alleged urban sustainability, with the urban agenda as a backdrop and under the elementary principles of spatial justice, the results reveal areas under-supplied with activities and areas that succumbed to central tertiarisation. The model is replicable and exportable to other case studies in Spain.
Keywords: Downscaling; Intra-urban; Buildings; CAT Files; Spatial justice